Refusing the False Choice Between Individual and Collective Liberation: Interview with Blair Taylor - Kolozova, Katerina; Saveski, Zdravko; Taylor, Blair (Identities: Journal for Politics, Gender and Culture, 2019)
The following interview is an email exchange with the author, which was conducted as a follow up to the School for Politics and Critique 2019: Municipal Organizing and Left-wing Environmental Solutions. The questions were prepared by Katerina Kolozova and Zdravko Saveski. Author(s): Katerina Kolozova, Zdravko Saveski and Blair Taylor Title (English): Refusing the False Choice Between Individual and Collective Liberation: Interview with Blair Taylor Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 32-37 Page Count: 6 Citation (English): Katerina Kolozova, Zdravko Saveski and Blair Taylor, “Refusing the False Choice Between Individual and Collective Liberation: Interview with Blair Taylor,” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 32-37.